The message of Galatians only one way - Stott, John Robert Walmsley 1921- (Leicester, UK IVP, 1968)
Includes bibliographical references.
"The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990". 1986 reprint : Originally published under the title "Only one way".
Keywords: Bible. N.T. Galatians -- commentaries